(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2021)
Background: Diabetic nephropathy (DN) is caused by chronic complications due to microvascular changes in patients with T2DM associated with the inflammatory process. Neutrophils to Lymphocyte Ratio (NLR) is a ratio that can describe the acute and chronic inflammatory systemic and allegedly the inflammatory process in the kidney. This study aims to determine the association between NLR with diabetic nephropathy in patients with type 2 diabetes. Method: This study is an analytical study with a case-control design. Samples were taken from the medical record installation room at Sanglah General Hospital Denpasar. Data was taken by using a simple random sampling method for 1 year that is 2017 according to inclusion and exclusion criteria. Statistical analysis including univariate analysis, normality test, Mann Whitney test, chi-square test, and AUC was done by using SPSS 23. Results: 143 sample data were used in this study with an average age of 62 years old (S.D 11.5). Median NLR for DN as case group were found 3.19 ranges within 1.19-29.2 while median NLR for non-DN as control group were found 3.2 (0.82-15.5) with p=0.000. NLR proportion ≥2.5 in the non-DN group was found 30 (42.2%) and DN group were found 49 (68%) with p=0.002. Risk analysis between NLR and Diabetic nephropathy obtained OR 2.91 and 95% CI: 1.45 - 5.76. Other variables such as age, sex, and diabetic status towards NLR levels were found not statistically significant. The results of AUC were 69.6% with 95%CI within the range (61.1% -78.2%). Conclusion: There is a significant association between NLR and diabetic nephropathy which potentially reflects the inflammation of the diabetic nephropathy process.